The Effect of NPK Fertilizer on Seed Quality and Yield of Jack Bean (Canavalia ensiformis) and Velvet Bean (Mucuna pruriens) - Maulana, Wahyudi; NUR AULIYA, SUKMA; Nurraffa, Muhammad Fatiharizqi; Subhan Abdurrazaq, Diffa Ali; Trisnaningsih, Umi (Jurnal Agrosci, 2025)
Background. Mucuna pruriens and Canavalia ensiformis are two types of legumes that can be utilized as plant-based protein sources to replace soybeans. However, these plants yield less than soybeans. Aim. This study aims to determine the effect of NPK fertilizer doses on the yield and quality of M. pruriens and C. ensiformis seeds. Methods. This research was conducted in Nanggela Village, Mandirancan District, Kuningan Regency, West Java, from June to November 2024. The experimental design used was a Randomized Block Design (RBD) with ten treatment combinations between two species of koro beans with NPK fertilizer doses (150, 225, 300, 375, and 450 kg ha-1). Result. The research results show that applying NPK fertilizer doses does not significantly affect the N, P, and K content in jack bean or velvet bean seeds, nor the total protein and fat content. Conclusion. The weight of pods per plot and the weight of seeds per plot were significantly influenced by the NPK fertilizer dosage and the species of koro. Implementation. Fertilizing using NPK efficiently can improve crop yields, soil quality, and the nutrients present in plants.